Evaluation of Stool Short Chain Fatty Acids Profiles in the First Year of Life With Childhood Atopy-Related Outcomes - Cheng, Hsin Yue; Chan, James Chun Yip; Yap, Gaik Chin; Huang, Chiung-Hui; Kioh, Dorinda Yan Qin; Tham, Elizabeth Huiwen; Loo, Evelyn Xiu Ling; Shek, Lynette P. C.; Karnani, Neerja; Goh, Anne; Van Bever, Hugo P. S.; Teoh, Oon Hoe; et al. (Frontiers in Allergy, 2022)
Short chain fatty acids (SCFAs) are the main intestinal intermediate and end products of metabolism of dietary fibres/polyphenols by the gut microbiota. The aim of this study was to evaluate the biological implication of stool SCFA profiles determined in the first year of life on the clinical presentation of allergic outcomes in childhood. From the Growing Up in Singapore Towards healthy Outcomes (GUSTO) cohort, a sub-cohort of 75 participants was recruited. Scheduled questionnaire data was collected for cumulative prevalence of physician-diagnosed eczema, wheezing with the use of nebuliser, and allergen sensitisation till the age of 8 years. Stool samples collected at week 3 and months 3, 6 and 12 were quantitated for 9 SCFAs using LC/MS/MS. SCFA data were grouped into lower (below the 25th) and higher (above the 75th percentiles) categories. Generalized Linear Mixed Models was employed to analyse longitudinal association between SCFAs and atopy-related outcomes. Children with lower stool butyric acid levels (≤25th percentile) over the first 3 time points had higher odds ratio (OR) for wheezing (adjOR=14.6), eczema (adjOR=13.2), food sensitisation (adjOR=12.3) and combined outcomes of both wheezing and eczema (adjOR=22.6) till age 8 years, compared to those with higher levels (≥75 percentile). Additionally, lower longitudinal levels of propionic acid (≤25th percentile) over 4 time points in first year of life was associated with recurrent wheezing (2 episodes) till 8 years (adjOR=7.4) (adj p<0.05). Our results suggest that relatively low levels of gut SCFAs in early life are associated with increased susceptibility to atopic-related outcomes in childhood.